2017
DOI: 10.1186/s12876-017-0602-0
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease (IBD) pharmacotherapy and the risk of serious infection: a systematic review and network meta-analysis

Abstract: BackgroundThe magnitude of risk of serious infections due to available medical therapies of inflammatory bowel disease (IBD) remains controversial. We conducted a systematic review and network meta-analysis of the existing IBD literature to estimate the risk of serious infection in adult IBD patients associated with available medical therapies.MethodsStudies were identified by a literature search of PubMed, Cochrane Library, Medline, Web of Science, Scopus, EMBASE, and ProQuest Dissertations and Theses. Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 55 publications
1
43
0
1
Order By: Relevance
“…Usually, the conventional therapies for IBD can be grouped into the two following approaches: anti-inflammation, e.g., corticosteroids, mesalazine, and cyclosporine; and anti-microbial, including ornidazole and rifaximin [24]. Ordinarily, these drugs are useful for treating mild to moderate IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the conventional therapies for IBD can be grouped into the two following approaches: anti-inflammation, e.g., corticosteroids, mesalazine, and cyclosporine; and anti-microbial, including ornidazole and rifaximin [24]. Ordinarily, these drugs are useful for treating mild to moderate IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Among studies of combination therapy, neither randomised controlled trials nor network meta‐analyses have demonstrated an increased risk of serious infections in patients receiving combination therapy versus anti‐TNF monotherapy . These results should be interpreted with caution given the relatively small numbers and short duration of follow‐up of patients in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…37 Among studies of combination therapy, neither randomised controlled trials nor network meta-analyses have demonstrated an increased risk of serious infections in patients receiving combination therapy versus anti-TNF monotherapy. 33,38 These results should be interpreted with caution given the relatively small numbers and short duration of follow-up of patients in clinical trials. Nevertheless, higher rates of opportunistic, but not serious, infections have been reported in retrospective case-control and cohort studies of patients treated with combination therapy.…”
Section: CDmentioning
confidence: 94%
“…Previous literature, plagued with inconsistencies and conflicting evidence, have estimated the risk of infections with IBD pharmacotherapy between 0.5% and 30%. 2 A study of 2600 IBD patients indicated that active disease and use of thiopurines were independent risk factors for serious viral infections. 3 Meta-analyses for different biologics used in IBD have failed to report a significantly greater risk of infection for most of them, although the data mostly comes from RCTs.…”
mentioning
confidence: 99%
“…One study reported disease relapse rate of 27% within first year after TNFαinhibitor discontinuation. 2 Patients who develop disease flares may require higher doses of immunosuppressants to achieve control and may even require hospitalization and/or endoscopic eval-uation. The SARS-CoV-2 virus has shown rapid transmission in health-care facilities where other infected individuals arrive for their care and even asymptomatic carries could transmit the disease.…”
mentioning
confidence: 99%